2016
DOI: 10.1084/jem.20160961
|View full text |Cite
|
Sign up to set email alerts
|

Resetting microbiota by Lactobacillus reuteri inhibits T reg deficiency–induced autoimmunity via adenosine A2A receptors

Abstract: He et al. show that T reg deficiency markedly induces autoimmunity and shifts gut microbiota. Remodeling microbiota by Lactobacillus reuteri was found to inhibit autoimmunity via the metabolite inosine, which interacts with the adenosine A2A receptor. This finding establishes a link between the gut microbiota, A2A receptors, and autoimmunity induced by T reg cell deficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
157
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(173 citation statements)
references
References 87 publications
(120 reference statements)
12
157
1
3
Order By: Relevance
“…For example, as mentioned above, studies in the lab of Versalovic showed that L. reuteri strain ATCC PTA 6475 produces vitamin B 12 and histamine; the probiotic reduced tumor necrosis factor‐α production via a protein kinase A–dependent mechanism . Subsequently, in our lab, a different strain of L. reuteri DSM 17938, which does not produce vitamin B 12 or increase histamine levels, did not reduce gut inflammation in rat intestine ex vivo, but prevented NEC and markedly attenuated multiorgan inflammation in the scurfy mouse . The mechanism involved, in contrast, was the activation of an adenosine A 2A receptor.…”
Section: Myths and Mysteriesmentioning
confidence: 55%
See 3 more Smart Citations
“…For example, as mentioned above, studies in the lab of Versalovic showed that L. reuteri strain ATCC PTA 6475 produces vitamin B 12 and histamine; the probiotic reduced tumor necrosis factor‐α production via a protein kinase A–dependent mechanism . Subsequently, in our lab, a different strain of L. reuteri DSM 17938, which does not produce vitamin B 12 or increase histamine levels, did not reduce gut inflammation in rat intestine ex vivo, but prevented NEC and markedly attenuated multiorgan inflammation in the scurfy mouse . The mechanism involved, in contrast, was the activation of an adenosine A 2A receptor.…”
Section: Myths and Mysteriesmentioning
confidence: 55%
“…In the mouse, as in the human, there is early‐onset dermatitis, progressive multiorgan inflammation, and death within the first month of life caused by a lymphoproliferative syndrome . Oral administration of L. reuteri DSM 17938 markedly prolonged survival and reduced symptoms; treatment also reduced multiorgan inflammation by inhibiting T H 1 and T H 2 cells and their associated cytokines …”
Section: Preclinical Trials and Mechanism Of Action In Inflammatory Dmentioning
confidence: 99%
See 2 more Smart Citations
“…The microbiota also influences the immune system by producing factors that promote Treg induction [172,173].…”
Section: Gut Microbiotamentioning
confidence: 99%